Children with hypoplastic left heart syndrome have lower quality of life than healthy controls and children with other illnesses. (29th August 2017) - Dempster, Nicole; Cua, Clifford L; Wernovsky, Gil; Caris, Elizabeth; Neely, Trent; Allen, Robin; Butz, Catherine
Abstract: Objective: Previous studies suggest that children with congenital cardiac diagnoses report lower quality of life when compared with healthy norms. A few studies have evaluated quality of life specifically in children born with hypoplastic left heart syndrome, a condition requiring several surgeries before age three. The aim of this study was to use an empirically validated and standardised measure – the Pediatric Quality of Life Inventory – to evaluate quality of life in children with hypoplastic left heart syndrome and compare the findings with similar, medically complicated samples. Methods: The parent-report Pediatric Quality of Life Inventory was administered, and demographic information was collected through an internet portal. A total of 121 caregivers of children with hypoplastic left heart syndrome responded. The sample included children aged 2–18 years (M=10.81 years). Independent sample t-tests were used to compare our sample with published norms of healthy children and children with acute or chronic illnesses. Results: Children with hypoplastic left heart syndrome were rated as having significantly lower overall quality-of-life scores (M=59.69) compared with published norms of children without medical diagnoses (M=83.00) and those with acute (M=78.70) or chronic (M=77.19) illnesses (p<0.001). Children with hypoplastic left heart syndrome complicated by a stroke or seizure (15%) reported the lowest quality of life. The results held for all subscales (p<0.001). Conclusions: Children with hypoplastic left heart syndrome appear to be a significantly vulnerable population with difficulties in functioning across psychosocial domains and across the age span. Further research is required to facilitate early identification of the need for resources for these children and families, especially for children who experience additional medical complications.